Epidemiology of Burns During Confinement Period Experience of the Burns Department of Marrakech University Hospital - Elatiqi, Oumkeltoum; Zinedine, I.; Alami, Z.; Lamaalla, Y.; Elamarani, M. D.; Benchamkha, Y. (International Journal of Innovative Research in Medical Science, 2022)
The coronavirus disease pandemic has spread to every corner of the world and has affected our practice as healthcare professionals, Morocco has experienced a period of strict containment on March, April and May 2020. This confinement gave notable social and economic changes. Through this analytic study we compare the epidemiology of burns admitted to the burn’s unit of the university hospital Mohammed VI of Marrakech on March, April and May 2020 and March, April and May2019, we have noticed significant decrease of cases and particularly severe cases and also the importance of domestic accidents as the principal cause.